Israel's nuclear whistleblower - Mitchell, Christopher; Magnetic North Films ([Australia] : BBC, 2006)
This is the interview the Israeli government doesn't want the world to see. In 1986, Israeli Mordechai Vanunu went to a British newspaper,'The Sunday Times', with information about Israel's nuclear weapons program. Charged with espionage and treason, he was jailed for 18 years. Although he is now'free' he is still not allowed to use a mobile phone or the internet, speak to foreigners, approach borders and embassies, or leave the country. The Israeli government have done everything they can to prevent him publicly answering the charges brought against him. But the BBC secured an interview, in the Anglican cathedral of Jerusalem, without breaching any of the Israeli governments restrictions. In this film he explains why he blew the whistle and how he survived in jail and answers the charge that he betrayed his country.
Title from container
Producer for the BBC, Olenka Frenkiel ; edior, Karen O'Connor.
dvd format.
Keywords: Vanunu, Mordechai; Nuclear weapons -- Israel; Israel -- Defenses